Global emissions of polychlorinated naphthalenes from 1912 to 2050 - Yuyan Luo; Yechao Shen; Minghui Zheng; Guorui Liu (Nature Communications)
Abstract Polychlorinated naphthalenes (PCNs) are persistent organic compounds that are regulated by the Stockholm Convention. Here, we estimate historical emissions from PCN production and use (1912-1987) and unintentional emissions from 20 categories (2000-2020). A random forest regression model projects emissions for 2020-2050. A global high-resolution 1 km × 1 km PCN emissions inventory is developed for 2020. The results show that 468,014 t of PCNs were emitted from historical production, with 96.6% of emissions occurring during product use, the majority of cumulative PCN emissions (99.4%) entering the atmosphere. Total unintentional emissions from 2000–2020 are 11,534 t. Global emissions of PCNs are 293.5 t (15.8 kg TEQ) in 2020, with municipal waste incineration as the major source (98.0%) and West Central Asia being the major emission region. Future PCN emissions may experience fluctuations, with projected changes ranging from a decrease of 29% to an increase of 347%.